2012
DOI: 10.1175/jhm-d-11-074.1
|View full text |Cite
|
Sign up to set email alerts
|

The 2009/10 Drought in China: Possible Causes and Impacts on Vegetation

Abstract: Several provinces of China experienced an intense drought episode during 2009 and 2010. The drought was particularly severe in southwestern and northern China, where the accumulated precipitation from May 2009 to April 2010 was about 25% less than normal. The decline of accumulated precipitation over northern China was mostly noticeable during the summer season of 2009 and it was comparable to recent dry episodes. The southwestern China drought resulted from a sequence of dry months from summer 2009 to winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(134 citation statements)
references
References 63 publications
5
129
0
Order By: Relevance
“…Before the data are gridded, an objective quality control procedure is applied (Hamada et al, 2011). Previous studies confirmed the high quality of the data (Rajeevan and Bhate, 2009;Krishnamurti et al, 2009;Wu and Gao, 2013). The rain-gauge network in China is dense except in climatologically dry regions, i.e.…”
Section: Observational Data and Indicessupporting
confidence: 65%
“…Before the data are gridded, an objective quality control procedure is applied (Hamada et al, 2011). Previous studies confirmed the high quality of the data (Rajeevan and Bhate, 2009;Krishnamurti et al, 2009;Wu and Gao, 2013). The rain-gauge network in China is dense except in climatologically dry regions, i.e.…”
Section: Observational Data and Indicessupporting
confidence: 65%
“…The detected Ex-1 (the biggest one) shown in Section 4.1 cover these area and period. While, the range of Ex-1 covers most of this latitude, that could be the result of atmospheric transport, and effect of drought-induced CO2 emissions in eastern Eurasia, discussed in Barriopedro et al [73]. The small region of high XCO2 in eastern North America is not associated with a high temperature or drought event.…”
Section: Spatial Patterns Of Extreme High Co2 Concentrations During Ementioning
confidence: 94%
“…With global climate change, China, whose per capita cultivated land is only 32% that of the global average, has suffered severe droughts in recent decades [4,20]. The economic losses caused by droughts far exceed those caused by other natural disasters.…”
Section: Introductionmentioning
confidence: 99%